Two-Dimensional Mathematical Model Named Tuna-Wq For Water Quality Analysis - Chong, Michael Sueng Lock (2018)
The main purpose of this study is to develop an in-house two-dimensional water quality model, codenamed TUNA-WQ, as an alternative to currently available water quality models, which are often either difficult to set up and limited in their application or are licensed.